Some main ideas about the concept of positivism and authority in Joseph Raz (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
There are different versions of legal positivism. We place the approach to this topic in the conception of Joseph Raz. In it, the author considers law as a system that claims authority. The question then arises as to whether or not citizens have to recognize said authority, and if so, how this would be justified. This question, that of the justification of the obligation to obey the law, is addressed by Raz and along with it he also deals with the complex problem of the right to dissent, whether through civil disobedience or through conscientious objection.
Keywords: positivism; authority; obedience to law